Drivers Of Innovation Without Formal R&D: Selected cases of Indonesian firms - Erman Aminullah; Trina Fizzanty; Qinan Maulana B Soesanto (STI Policy and Management Journal, 2018)
The objective of this study is to have deep understanding on why and how firms engaging in innovation without formal R&D. Three cases of firms in machinery and food processing sectors were studied. The cross cases analysis found that types and sources of innovation vary according to business areas, technology field, and technological capability level of each firms. Firms innovate without formal R&D through  it’s particular ways, and it is driven by firm’s specific resources namely management vision and leadership,  integrated business system, and entrepreneurship and networking. The conceptual contribution of this study is an enrichment to “learning by using” with a new variant the so called “mastering from using”. Nevertheless, innovation without formal R&D is deficient in absorptive capacity (AC), it implies that non-R&D and informal R&D firms should  invest in R&D to develop AC and increase technology adoption. Goverment policy by using  R&D financing support and tax incentives should be directed at the innovative low-tech (LT) as well as low and medium-tech (LMT) industries, which will have produced higher results through innovation with informal and/or non R&D actvities.   Keywords: innovation drivers, innovation types, innovation sources, non-R&D, informal R&D